Spatialité financiarisée. L’écueil du patrimoine judiciaire - Stéphanie Boufflet; Nicolas Henry (In Situ)
As the holder of an exceptional heritage, the French Ministry of Justice is now faced with problems of managing its heritage. It thus increasingly resorts to funds and private partnerships which enable it to give new activity to these buildings.However, these changes of use do not necessarily lead to a change of identity, which is not without posing problems for these emblematic places of the city, representative by their architecture of the power and the integrity of the state. Beyond these issues, it is also a change in management in which cities must now engage in long and complex public - private partnerships, again posing questions of integrity and prerogative, such as the conversion of the city of Caen former high Court.